2018
DOI: 10.1063/1.5039595
|View full text |Cite
|
Sign up to set email alerts
|

Reference Correlation of the Viscosity of n-Hexadecane from the Triple Point to 673 K and up to 425 MPa

Abstract: A new correlation for the viscosity of n-hexadecane is presented. The correlation is based upon a body of experimental data that has been critically assessed for internal consistency and for agreement with theory. It is applicable in the temperature range from the triple point to 673 K at pressures up to 425 MPa. The overall uncertainty of the proposed correlation, estimated as the combined expanded uncertainty with a coverage factor of 2, varies from 1% for the viscosity at atmospheric pressure to 10% for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 95 publications
2
14
0
Order By: Relevance
“…These results agree well with existing literature data with an average absolute relative deviation of 2% across all selected literature sources. The experimental data obtained here may be useful in the development of a more wide-ranging correlation for the viscosity of hexadecane …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results agree well with existing literature data with an average absolute relative deviation of 2% across all selected literature sources. The experimental data obtained here may be useful in the development of a more wide-ranging correlation for the viscosity of hexadecane …”
Section: Discussionmentioning
confidence: 95%
“…The experimental data obtained here may be useful in the development of a more wide-ranging correlation for the viscosity of hexadecane. 26…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In parallel, these experimental values were compared to the calculated hexadecane film thickness. The pressure-viscosity coefficient of hexadecane was deduced from the data presented by Meng et al [40] fitted with Roelands' equation [41] and a viscosity of 3 mPa.s. The resultant value, α = 10 GPa −1 , was low, leading to the use of Moes-Venner prediction [42] to calculate the hexadecane film thickness.…”
Section: Tribology: Irismentioning
confidence: 99%
“…The results are listed in Table . The results were compared with the experimental data reported by Trusler et al In addition, Meng et al reported a reference correlation of the viscosity of n -hexadecane, the data of this work were also compared with the calculated results of Meng et al The deviations are shown in Figure . In general, our results agree with the values of the two literatures.…”
Section: Resultsmentioning
confidence: 82%